The impact of compulsory health service on physicians and burnout in a province in eastern anatolia - Taycan, O.; Erdo?an Taycan S.; Çelik C. (Turkish Association of Nervous and Mental Health, 2013)
Objective: The Compulsory Health Service (CHS) for physicians has been in place since 2005. The aim of this study was to investigate the impact of the CHS on physicians and the factors associated with burnout. Method: The sample group consisted of all physicians working within the province of Mus in this cross-sectional, descriptive, epidemiological study. All participants were assessed using the Maslach Burnout Inventory (MBI), the Beck Depression Inventory, the Job Satisfaction Scale (JSS), the Satisfaction with Life Scale, the Professional Quality of Life Scale (ProQOL) and the General Health Questiannaire-12, along with a detailed sociodemographic and professional data form. Results: A total of 139 physicians participated in this study, and 100 of them (71%) were fulfilling the CHS. Physicians who fulfilled the CHS were found to have lower levels of job satisfaction and professional quality of life. They also had higher levels of depression, general psychiatric symptoms, and psychological stress. The relationships between the level of burnout in physicians fulfilling the CHS and the scores from the scales used in the study were statistically significant except those between MBI-Personal Accomplishment, JSS, and ProQOL-Compassion Fatigue subscales. The extent of depressive symptoms and the daily number of patients were predictors of all three subscales of burnout. Job satisfaction was a predictor of both emotional exhaustion and depersonalization, while life satisfaction was a predictor of emotional exhaustion, and gender was a predictor of personal accomplishment. Conclusion: The level of burnout among physicians who had fulfilled the CHS was high. The factors and predictors associated with burnout were discussed.
PubMed ID: 24049008
Keywords: Burnout; Depression; Job satisfaction; Physicians